Study on Joint Damage of Double Prefabricated Fragments Penetrating Finite Thickness Concrete - Zhenning Wang; Junhui Yang; Jianping Yin; Xudong Li; Rui Shi; Jianya Yi (Shock and Vibration)
In order to study the joint damage mechanism of multiple prefabricated fragments to finite thickness concrete targets, experiments on the damaging effect of a single fragment on a 300 × 300 × 100 mm concrete target were carried out, and the reliability of the simulation calculation model of single fragment damage to concrete was verified. On this basis, according to the trajectory of two fragments penetrating concrete, the double fragment penetration is divided into two penetration situations, that is, coplanar and heterogeneous. The orthogonal optimization method is used to carry out the joint damage simulation calculation of the double fragments to the concrete target by changing the fragment velocity, penetration angle, fragment spacing, and other factors. The simulation results show that the relationship between joint damage and fragment spacing is the largest when the fragment trajectories are coplanar, and the partial least squares regression coefficients affecting the joint damage time and surface joint length are 0.70 and 0.68 respectively. When the trajectory is different, the joint damage mode is relatively complex. Based on this, the joint damage degree analysis method between fragments is established, and each variable can explain 73.8% of the joint damage degree. It is found that the joint damage of the front pit area is the largest when the fragment is in different planes, and the PLS regression coefficient is −0.44. The hypothesis that joint damage is easy to occur in the area of the intersection line on the back of the target is analyzed and verified.